2020
DOI: 10.3390/s20030636
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Navigation Systems for Visually Impaired Persons: Mapping the Features of Existing Technologies to User Needs

Abstract: Currently, several outdoor navigation and orientation electronic traveling aid (ETA) solutions for visually impaired (VI) people are commercially available or in active development. This paper’s survey of blind experts has shown that after outdoor navigation, the second most important ETA feature for VI persons is indoor navigation and orientation (in public institutions, supermarkets, office buildings, homes, etc.). VI persons need ETA for orientation and navigation in unfamiliar indoor environments with embe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…Previous literature includes, for indoor environments, reviews of navigation and location systems [15,16], and also of WBAN [17], for VIP (Visually Impaired People). In the case of hearing-impaired people, reference [18] includes a review on assistive listening devices.…”
Section: A Wireless Communications and Location Systems For Impairedmentioning
confidence: 99%
“…Previous literature includes, for indoor environments, reviews of navigation and location systems [15,16], and also of WBAN [17], for VIP (Visually Impaired People). In the case of hearing-impaired people, reference [18] includes a review on assistive listening devices.…”
Section: A Wireless Communications and Location Systems For Impairedmentioning
confidence: 99%
“…The subject is quite comprehensive when discussing the composition of models, systems, and objectives [ 23 ]. Although the use of such systems allows the location, tracking, and navigation of targets in internal environments, their construction processes are established to meet precision and punctuality requirements defined jointly by the users responsible for the development of the system and the limits set by the hardware and software layers [ 24 ].…”
Section: Related Workmentioning
confidence: 99%
“…Plikynas et al indicated that there are currently many solutions available to assist in the navigation of people with visual impairments in previously known indoor environments [ 24 ]. The authors suggested that indoor environments have more significant complexities than outdoor environments, and alerts should be given more quickly to avoid accidents.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations